Adhesive composition for optical film based on waste plastic and preparation method of adhesive composition

By copolymerizing the oligomer of the pyrolytic product of waste plastic with modified titanium dioxide, high refractive index optical adhesives are prepared, and the problems of cumbersome sources of adhesive raw materials are solved, and the effect of efficient utilization of waste plastics and cost reduction is achieved.

CN120272127APending Publication Date: 2025-07-08NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510192660.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-07-08

AI Technical Summary

Technical Problem

The source of existing adhesive raw materials is cumbersome and expensive, and it is difficult to effectively utilize waste plastics, resulting in high production costs and serious environmental pollution.

Method used

By synthesizing the waste plastic pyrolytic product into polypropylene alcohol and polyacrylic acid, the oligomer is further synthesized, and copolymerized with modified titanium dioxide and polysulfur polymer, photoinitiator, crosslinking agent and antistatic agent are added to prepare a high refractive index optical adhesive.

Benefits of technology

It improves the elasticity and brightness of the adhesive, reduces the shrinkage rate, expands the application field, and realizes efficient recycling and cost reduction of waste plastics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120272127A_ABST
    Figure CN120272127A_ABST
Patent Text Reader

Abstract

The invention discloses an adhesive composition for an optical film based on waste plastics and a preparation method, and the preparation method comprises the following steps: in the preparation process of an adhesive, modifying titanium dioxide through oleic acid and mPEO, and then copolymerizing a sodium persulfide solution and the modified titanium dioxide to prepare a high-refractive-index substance, so that the high refractive index of the adhesive can be improved; the surface treatment is performed by incorporating metal oxide particles, thereby improving dispersibility in the adhesive layer and in the composition for coating the layer, and further improving the luminance of the adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adhesives for bonding optical components and substrates such as glass, and particularly relates to an adhesive composition for an optical film based on waste plastics and a preparation method thereof. Background Art

[0002] The market demand for thin-film transistor liquid crystal (TFT-LCD), as a new generation of mainstream display devices, has further increased; among them, the optical films (brightness enhancement film accounting for 29%, diffusion film accounting for 6%, and reflection film accounting for 2%) of the backlight module that provides high-brightness and uniform light sources are one of the modules with the highest technical content, accounting for about 15% of the total cost of the TFT-LCD of the new generation of mainstream display devices, and the market demand is huge. The brightness enhancement film (BEF), also known as a prism sheet or a light collecting sheet, is a film or sheet that can improve the luminous efficiency of the entire backlight system in the liquid crystal display backlight module, and was first invented and used by the 3M Company of the United States. Using a special prism structure and through optical principles such as refraction, total reflection, and light accumulation, the brightness enhancement film can concentrate the light in all directions towards the central viewing angle, thereby enhancing the brightness of the LCD panel and controlling the viewing angle, and is an essential core part of liquid crystal display devices. There are still problems such as a high degree of dependence on imports for key materials (such as prism resins, adhesives, etc.), key equipment, and processes. Therefore, it is necessary to prepare key materials such as adhesives with high brightness, high strength, and low shrinkage rate.

[0003] The plastic industry has been very mature. Although plastics have brought great convenience to people's production and life, due to their high stability, difficulty in degradation, and other characteristics, serious environmental problems have been brought about. Existing plastic treatment methods include landfilling, incineration, pyrolysis, etc. Due to the high stability and difficulty in degradation of plastics, landfilling is likely to cause soil pollution problems; the incineration method will release a large amount of gases such as carbon dioxide and sulfur dioxide, thereby causing air pollution; the pyrolysis method is favored by people because its products can be further utilized, but due to random chain scission, the added value of the pyrolysis products of plastics is low, so it is necessary to further explore high-added-value products of plastic pyrolysis products.

[0004] CN114867823B discloses a continuous method for converting waste plastics into recycled materials for ethylene polymerization or for the production of normal alpha-olefins; which includes selecting waste plastics containing polyethylene or polypropylene, and then passing the waste plastics through a pyrolysis reactor to pyrolyze at least a part of the polyolefin waste and generate a pyrolysis effluent. The pyrolysis effluent is separated into waste gas, naphtha / diesel fraction, heavy fraction and char. The naphtha / diesel fraction is sent to the crude oil unit of an oil refinery to recover a straight-run naphtha fraction (C5-C8) or a propane / butane (C3-C4) fraction therefrom. Then the straight-run naphtha fraction or the propane and butane (C3-C4) fraction is sent to a steam cracking unit to produce propylene / ethylene.

[0005] CN117120580A discloses systems and methods for treating pyrolysis oil derived from plastics; under reaction conditions sufficient to produce a gas stream and a liquid stream containing propylene, the pyrolysis oil derived from plastics or plastics is treated in a catalytic cracking unit and a thermal cracking unit. The liquid stream is further treated to produce additional propylene.

[0006] There are many public reports on the preparation of acrylic polymer adhesives. CN106471085B discloses an adhesive composition for optical elements, an optical element containing the same, and an optical display device including the same, wherein the composition contains an acetoacetoxy group-containing (meth)acrylic copolymer, a metal chelating curing agent, and a trifunctional or higher-functional isocyanate curing agent. The (meth)acrylic copolymer has an acid value of 0 mg KOH / g, shows good adhesion to a polarizing plate, thereby providing good reprocessability and processability, and shows good properties in terms of heat resistance and resistance to heat and humidity.

[0007] CN115537124A discloses a post-curable optical adhesive, an OCA optical adhesive and a preparation method thereof, including: a mixture of a methacrylate copolymer and a methacrylate monomer; the methacrylate copolymer and the methacrylate monomer include an epoxy group. It solves the problem that there is currently no OCA optical adhesive that combines fluidity before curing and stability after curing.

[0008] CN113227297A discloses an adhesive composition for an optical film. The adhesive composition contains a (meth)acrylic polymer and a crosslinking agent. The above (meth)acrylic polymer contains an amide group-containing monomer and an alkoxy (meth)acrylate alkyl ester as monomer units, and contains 20-80 wt% of the above alkoxy (meth)acrylate alkyl ester relative to the total amount of 100 mass of the monomer units constituting the above (meth)acrylic polymer. It meets the high bonding reliability requirements of the optical film for the adhesive layer and the durability at high temperatures.

[0009] Although the above-mentioned well-known technologies can all prepare adhesives using acrylic acid / methyl methacrylate as raw materials, the existing adhesive raw materials are derived from chemical raw materials that are cumbersome to prepare and expensive. According to existing market research, acrylic acid is 6,000 yuan per ton, and methyl acrylate is 7,690 yuan per kilogram. The adhesives prepared from them are expensive; while waste plastics are 4,000 yuan per ton, which greatly reduces the production cost. At the same time, it promotes the recycling of waste plastics and the vigorous development of the "carbon circular economy". Summary of the Invention

[0010] The purpose of this part is to outline some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this part, as well as in the abstract and title of the present application, to avoid obscuring the purpose of this part, the abstract, and the title. However, such simplifications or omissions cannot be used to limit the scope of the present invention.

[0011] In view of the above and / or problems existing in the prior art, the present invention is proposed.

[0012] The first aspect of the present invention provides a method for preparing a binary or polyhydric allyl alcohol composition with hydroxyl groups. The method includes: performing an oxidation reaction on plastic oil and syngas in an inert gas reaction atmosphere, and after cooling, performing a catalytic hydrogenation reaction on the hydroformylation product and hydrogen under the condition of a catalyst.

[0013] According to the method of the present invention, the conditions of the oxidation reaction include: the reaction temperature is 80 - 120°C, the reaction time is 20 - 40 min, and the stirring speed is 700 - 1000 rpm; preferably, the reaction temperature is 100 - 110°C, the reaction time is 25 - 35 min, and the stirring speed is 800 - 900 rpm.

[0014] According to the present invention, the conditions of the catalytic hydrogenation reaction of the catalyst include: the reaction temperature is 100 - 400°C, the reaction time is 8 - 12 h, the heating rate is 2 - 10°C / min, the hydrogen flow rate is 50 - 60 cm3 / min, and the pressure is 60 - 90 bar; preferably, the reaction temperature is 350 - 400°C, the reaction time is 9 - 11 h, the heating rate is 5 - 8°C / min, the hydrogen flow rate is 50 - 60 cm3 / min, and the pressure is 70 - 85 bar.

[0015] According to the present invention, the syngas is CO / H2 = 0.9 - 1.5 (molar ratio), preferably, the syngas is CO / H2 = 1 - 1.2 (molar ratio), and the inert gas is argon.

[0016] According to the present invention, the plastic oil is 10 - 60 parts by weight, preferably 30 - 50 parts by weight.

[0017] According to the present invention, the hydroformylation product is 20 to 70 parts by weight, preferably 40 to 50 parts by weight.

[0018] According to the present invention, the catalyst is a commonly used commercial catalyst such as Pt, Ni, Pd, etc.; preferably, the catalyst is Ni / SiO₂.

[0019] The second aspect of the present invention provides a method for preparing a binary or polyacrylic acid composition with a carboxyl group, the method comprising: mixing palladium acetate with an organic solution, preparing plastic oil, formic acid and CO by using standard Schlenk technology, and preferably the circulating gas is nitrogen.

[0020] According to the present invention, the plastic oil is 20 to 40 parts by weight, preferably 25 to 35 parts by weight.

[0021] According to the present invention, the organic solvent is a low-carbon organic compound, preferably butane, more preferably 1,4-bis(diphenylphosphinyl)butane, 1,4-bis(diphenylphosphino)butane.

[0022] According to the present invention, the organic solvent is 40 to 80 parts by weight, preferably 50 to 70 parts by weight.

[0023] According to the present invention, the palladium acetate is 20 to 40 parts by weight, preferably 26 to 40 parts by weight.

[0024] According to the present invention, the reaction conditions of the standard Schlenk technology include: the reaction pressure is 40 to 60 bar, the stirring rate is 200 to 400 rmp, and the reaction time is 12 to 18 h; preferably, the reaction pressure is 45 to 55 bar, the stirring rate is 300 to 350 rmp, and the reaction time is 14 to 16 h.

[0025] According to the present invention, the formic acid solution is 10 to 20 parts by weight, and the CO flow rate is 40 to 70 cm³ / min; preferably, the formic acid solution is 12 to 16 parts by weight, and the CO flow rate is 50 to 60 cm³ / min.

[0026] The third aspect of the present invention provides one or more (bromo)phenyl acrylate oligomers. The oligomers are obtained by polymerizing the above-mentioned (bromo)acrylates as monomers. The (bromo)phenyl acrylate can be (bromo)phenyl alkyl acrylate, (bromo)phenyl alkenyl acrylate, and (bromo)phenyl heterocyclic acrylate; wherein, the alkyl is preferably an alkyl having 1 to 20 carbon atoms, preferably 1 to 15 carbon atoms, and the alkyl may have one or more substituents. The alkenyl is preferably an alkenyl having 2 to 20 carbon atoms, preferably 2 to 10 carbon atoms, and the alkenyl may have substituents, and the substituents are preferably selected from alkyl having 1 to 10 carbon atoms, alkoxy having 1 to 10 carbon atoms, aryloxy having 6 to 10 carbon atoms, epoxy having 2 to 10 carbon atoms, and hydroxyl group, etc.; the heterocyclic group is preferably a heterocyclic group having 2 to 20 carbon atoms, preferably 2 to 10 carbon atoms, wherein the heteroatom is preferably selected from nitrogen and oxygen, and the heterocyclic group may have substituents, and the substituents are preferably selected from alkyl having 1 to 10 carbon atoms, alkoxy having 1 to 10 carbon atoms, aryloxy having 6 to 10 carbon atoms, epoxy having 2 to 10 carbon atoms, and hydroxyl group, etc.

[0027] Representative examples of the above-mentioned (bromo)phenyl acrylate include substances selected from the following: methyl (bromo)phenyl acrylate, ethyl (bromo)phenyl acrylate, butyl (bromo)phenyl acrylate, tetrahydrofurfuryl (bromo)phenyl acrylate, lauryl acrylate, isooctyl acrylate, isodecyl acrylate, 2-phenoxyethyl acrylate, 2-ethylhexyl (bromo)phenyl acrylate, isobornyl (meth)acrylate, dicyclopentenoxyethyl (meth)acrylate, dicyclopentadienyl (meth)acrylate, (meth)acrylic acid.

[0028] The fourth aspect of the present invention provides a method for preparing a metal oxide. The method includes: modifying TiO2 with oleic acid and mPEO, and carrying out ring-opening copolymerization with 1,2-dithioalkane to obtain a high refractive index material.

[0029] First, TiO2 surface is modified with oleic acid, and the modified TiO2 surface is modified with trimethylamine oxide. Subsequently, mPEO (molecular weight = 5000 g / mol) is modified according to the procedure proposed by Zalipsky and reacts with oleic acid-coated TiO2; the polysulfide polymer is copolymerized with the modified TiO2 in a sodium persulfide solution in a dichloroethane solution.

[0030] According to the present invention, the modified reaction conditions include: the reaction temperature is 80 to 120 °C, the heating rate is 20 to 40 °C / min, and the reaction time is 18 to 30 h; preferably, the reaction temperature is 100 to 110 °C, the heating rate is 26 to 34 °C / min, and the reaction time is 22 to 28 h.

[0031] According to the present invention, the oleic acid is 20 to 40 parts by weight, the tetramethyltetraphenylcyclotetrasiloxane is 1 to 10 parts by weight, the trimethylamine oxide is 0.1 to 2 parts by weight, and the TiO2 is 30 to 60 parts by weight; preferably, the oleic acid is 28 to 35 parts by weight, the tetramethyltetraphenylcyclotetrasiloxane is 4 to 7 parts by weight, the TiO2 is 45 to 60 parts by weight, and the trimethylamine oxide is 1 to 1.5 parts by weight.

[0032] According to the present invention, the mPEO is 26 to 48 parts by weight, the phosphoryl chloride is 0.8 to 1.6 parts by weight, and the triethylamine is 1.6 to 3 parts by weight; preferably, the mPEO is 32 to 40 parts by weight, the phosphoryl chloride is 1 to 1.5 parts by weight, and the triethylamine is 1.6 to 2 parts by weight.

[0033] According to the present invention, the Zalipsky conditions include: the reaction temperature is 15 to 30 °C, and the reaction time is 1 to 2 h; preferably, the reaction temperature is 20 to 28 °C, and the reaction time is 1.5 to 2 h.

[0034] According to the present invention, the copolymerization reaction conditions include: the reaction temperature is 30 to 80 °C, and the reaction time is 10 to 26 h; preferably, the reaction temperature is 40 to 60 °C, and the reaction time is 14 to 22 h.

[0035] According to the present invention, the polysulfide polymer is 30 to 50 parts by weight, the sodium tetrasulfide solution is 40 to 50 parts by weight, and the dichloroethane is 2 to 8 parts by weight; preferably, the polysulfide polymer is 36 to 48 parts by weight, the sodium tetrasulfide solution is 42 to 50 parts by weight, and the dichloroethane is 4 to 6 parts by weight.

[0036] According to the present invention, the composition may further include at least one of a photoinitiator, a crosslinking agent, and an antistatic agent, so as to further improve the refractive index and anti-shrinkage rate of the adhesive prepared from the composition.

[0037] According to the present invention, relative to 100 parts by weight of the binder composition, the content of the photoinitiator is 0.5 to 3 parts by weight, preferably 1 to 2 parts by weight. Relative to 100 parts by weight of the binder composition, the content of the crosslinking agent is 0.02 to 2 parts by weight, preferably 0.5 to 1.5 parts by weight. Relative to 100 parts by weight of the binder composition, the content of the antistatic agent is 0.008 to 1 part by weight, preferably 0.01 to 1 part by weight. Defining the photoinitiator, the crosslinking agent, and the antistatic agent within the foregoing ranges can further significantly improve: the refractive index of the blended binder, reduce the shrinkage rate of the binder, and increase the brightness of the composite film. More preferably, relative to 100 parts by weight of the binder composition, the photoinitiator is 1.2 to 2 parts by weight, the crosslinking agent is 0.8 to 1.2 parts by weight, and the antistatic agent is 0.05 to 1 part by weight. According to this preferred embodiment, the foregoing effects can be further improved.

[0038] According to the present invention, the photoinitiator can generate free radicals by light irradiation to initiate a photopolymerization reaction. In the optically transparent binder composition of the present invention, it can be one or more photoinitiators. There is no particular limitation on the photoinitiator used in the binder composition of the present invention, and any suitable photoinitiator known in the art can be used. Preferred examples of the photoinitiator include: anionic photoinitiators or cationic photoinitiators. Preferably, 2,4,6-trimethylbenzoyl diphenylphosphine oxide (TPO) is used as the photoinitiator. The photoinitiator TPO is selected because of its absorption advantage for light with a wavelength of 405 nm, minimizing the overlap with dithioalkane (λmax = 330 nm).

[0039] According to the present invention, the crosslinking agent enters the macromolecular structure chain during polymerization as a monomer or is added to the adhesive as a component and can be stored stably. Crosslinking reaction can only occur when heated to a certain temperature or under radiation conditions. Commonly used internal crosslinking agents include vinyl monomers such as acrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, methacrylic acid, hydroxyethyl methacrylate, hydroxypropyl methacrylate, divinylbenzene, N-hydroxymethyl acrylamide, and diacetone acrylamide.

[0040] According to the present invention, the antistatic agent can help prevent static electricity by reducing the surface resistance value of the acrylic binder. According to the present invention, an internal mixing type antistatic agent is preferred. Commonly used antistatic agents include ethoxylated aliphatic alkylamines, particularly preferably ethoxylated laurylamide, and glycerol monostearate (GMS), which are suitable for polyethylene and polypropylene used in an environment with low humidity and require an antistatic function with quick and long-lasting effects.

[0041] According to the present invention, the plastic pyrolysis product can maximize the recycling of plastics and realize the utilization of high-value-added products. Due to the utilization of waste plastics, the production cost of the adhesive can be further reduced; by selecting the high refractive index material defined in the present invention and through the synergistic effect of inorganic-organic, the refractive index of the adhesive can be increased, thereby maximizing the brightness of the adhesive and reducing the shrinkage rate of the composite film.

[0042] Advantages of the present invention:

[0043] (1) During the preparation process of the adhesive of the present invention, polyallyl alcohol and polyacrylic acid are first synthesized by pyrolysis oil oxidation, and then oligomers are further synthesized and added to the adhesive, which can improve the elasticity of the adhesive, enhance the efficient utilization of waste plastics, and further improve the recycling of high-value-added products of waste plastics.

[0044] (2) During the preparation process of the adhesive of the present invention, titanium dioxide is modified by oleic acid and mPEO, and then a high refractive index substance is prepared by copolymerization of sodium persulfide solution and the above-mentioned modified titanium dioxide, which helps to increase the high refractive index of the adhesive; by doping metal oxide particles for surface treatment, the dispersibility in the adhesive layer and the composition used for coating this layer can be improved, and the brightness of the adhesive can be further increased.

[0045] (3) The adhesive of the present invention is also filled with a composite material during the preparation process. The composite material is composed of a photoinitiator, a crosslinking agent, and an antistatic agent, which helps to increase the curing degree and strength of the adhesive. The antistatic agent helps to increase the antistatic effect of the composite material, thereby increasing the service life of the adhesive. Description of the drawings

[0046] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for the description of the embodiments will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings. Among them:

[0047] Figure 1 It is the technical route diagram in the embodiment of the present invention.

[0048] Figure 2 It is the nuclear magnetic spectrum diagram of the diallyl alcohol prepared in Example 1 of the present invention.

[0049] Figure 3 It is the nuclear magnetic spectrum diagram of the diacrylic acid prepared in Example 1 of the present invention. Detailed implementation manners

[0050] To make the above objects, features, and advantages of the present invention more apparent and understandable, the following specifically describes the embodiments of the present invention in detail in conjunction with the embodiments of the specification.

[0051] In the following description, numerous specific details are set forth in order to provide a thorough understanding of the present invention. However, the present invention may be implemented in other ways different from those described herein. Those skilled in the art can make similar generalizations without departing from the spirit of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed below.

[0052] Secondly, the so-called "one embodiment" or "embodiment" herein refers to specific features, structures, or characteristics that may be included in at least one implementation manner of the present invention. The phrase "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it an embodiment that is separate or selectively mutually exclusive with other embodiments.

[0053] In the embodiments of the present invention, the plastic oil is purchased from Xinji Haorui Petrochemical Co., Ltd.; gases such as syngas, argon, and nitrogen are purchased from Beijing Shenqian Technology Co., Ltd.; catalysts such as Ni / SiO2 are from Zibo Rongruida Powder Material Factory; palladium acetate, formic acid, (bromo)phenyl acrylate oligomer, oleic acid, mPEO, TiO2, tetramethyltetraphenylcyclotetrasiloxane, trimethylamine oxide, sodium tetrasulfide solution, and dichloroethane, etc. are purchased from Hubei Weishi Chemical Reagent Co., Ltd.

[0054] The measurement methods in the embodiments of the present invention:

[0055] The adhesion force is measured by a universal tensile testing machine (refer to national standard GB / T 14344); the light leakage is measured by a luminance meter (refer to the national standard); the micro-creep value is tested by a micro-creep tester (refer to national standard GBT 27595-2011); the refractive index is measured by HunterLab UltraScan PRO (refer to national standard GBT 7962.1-1987).

[0056] According to a particularly preferred embodiment of the present invention, the method includes:

[0057] Take 30 - 50 parts by weight of plastic oil, then transfer the mixture to a stainless steel Parr reactor, purge the reactor 2 - 3 times with Ar at room temperature (25°C), after the system reaches 100 - 110°C, introduce syngas (CO / H2 = 1 - 1.2, molar ratio) into the reactor, and the reaction time is 25 - 35 min. The mixture is stirred at 800 - 900 rpm throughout the process. Then load the catalyst (20 wt% Ni / SiO2) into a stainless steel tube reactor, and then pre-treat it at 350 - 400°C (heating rate: 5 - 8°C / min) for 3 - 4 h, and the hydrogen flow rate is 50 - 60 cm3 / min (SCCM). Then cool the reactor to 100 °C and pressurize it to 70 - 85 bar (H2) through a back-pressure regulator. Introduce 40 - 50 parts by weight of the hydroformylation product through an HPLC pump and react for 6 - 7 h.

[0058] Weigh 26 - 40 parts by weight of palladium acetate and 50 - 70 parts by weight of 1,4-bis(diphenylphosphino)butane, and place them in a clean and dry glass liner equipped with a drying stir bar. Install the glass liner inside a stainless-steel Parr autoclave and close the autoclave. Connect the autoclave to a Schlenk line and perform five cycles of evacuation and nitrogen filling. Using standard Schlenk techniques, add a cryopump thawed solution of 12 - 16 parts by weight of formic acid in dry 1,2-dichloroethane (DCE), and stir the mixture for 30 min. Then, using standard Schlenk procedures, add the required volume of degassed and dried plastic oil, 25 - 35 parts by weight, close the autoclave, and disconnect it from the Schlenk line. Transfer the autoclave to a polymerization block and connect it to a gas line. Flush the lines connected to the autoclave with nitrogen (N2) (3 × 30 bar). Flush the autoclave with carbon monoxide (CO), and then charge it with CO to 45 - 55 bar. Stir the autoclave at 300 - 350 rpm and heat it at the required temperature for 14 - 16 h.

[0059] In this example, more specifically, the (bromo)phenyl acrylate oligomer is copolymerized from (bromo)phenyl acrylate monomers with an ester group terminal carbon chain of 4 - 12 alkyl groups, (bromo)phenyl acrylate monomers with an epoxy group, (bromo)phenyl acrylate monomers with a hydroxyl group, and (bromo)phenyl acrylate monomers with a high Tg; wherein the mass fractions of each component monomer are 30 - 70 parts of (bromo)phenyl acrylate monomers with an ester group terminal carbon chain of 4 - 12 alkyl groups; 1 - 30 parts of (bromo)phenyl acrylate monomers with an epoxy group; 5 - 40 parts of (bromo)phenyl acrylate monomers with a hydroxyl group; and 10 - 50 parts of (bromo)phenyl acrylate monomers with a high Tg.

[0060] Add 28 - 35 parts by weight of oleic acid to a pre - dried round - bottom flask. To work in an air - free environment, the oleic acid is first degassed with three vacuum / nitrogen cycles and then further degassed at 120 °C for 2 h. Then cool the mixture to 90 °C under a nitrogen stream; when the target temperature is reached, add 4 - 7 parts by weight of tetramethyltetraphenylcyclotetrasiloxane all at once. After 5 min, inject 1 - 1.5 parts by weight of an aqueous solution of trimethylamine oxide all at once. Heat the flask to 100 - 110 °C at a heating rate of about 26 - 34 °C / min, and then react for 22 - 28 h under vigorous stirring. The solution changes from a clear pale - yellow mixture to a milky - white solution. Then centrifuge the crude product to precipitate a white solid composed of titanium dioxide NC covered with oleic acid. The particles are precipitated several times in ethanol to remove the excess ligands and are finally dispersed in hexane, chloroform, or DCM. Dissolve 32 - 40 parts by weight of mPEO in dry DCM and drop it into a solution of 1 - 1.5 parts by weight of phosphoryl chloride and 1.6 - 2 parts by weight of triethylamine in an ice bath. Warm the mixture to 20 - 28 °C and stir for 1.5 - 2 h. Under argon at 40 - 60 °C, add 42 - 50 parts by weight of a sodium sulfide solution to a vigorously stirred mixture of 4 - 6 parts by weight of dichloroethane and 60 - 80 parts by weight of degassed deionized water. Stir the reaction mixture at 40 - 60 °C for a further 14 - 22 h.

[0061] Based on 100 parts by weight of the binder composition, the photoinitiator, cross - linker, and antistatic agent are mechanically mixed in ratios of 1 - 2 parts by weight, 0.5 - 1.5 parts by weight, and 0.01 - 1 part by weight respectively. After mixing the above components evenly, under a nitrogen atmosphere, it is irradiated with ultraviolet light together with other additives to obtain the post - curable optical adhesive.

[0062] In summary, the technical solution provided by the present invention first synthesizes oligomers from waste plastic pyrolysis products, and then the oligomers with specific component contents can enhance the elasticity of the cured binder, which can improve the elasticity of the prepared binder composite film. Further, by modifying titanium dioxide with selected specific oleic acid and mPEO and copolymerizing with polysulfide polymers, the refractive index of the binder can be greatly increased, thereby improving the brightness of the binder composite film; in the binder composition, through the optimized ratio of the photoinitiator, cross - linker, and antistatic agent, the strength of the binder obtained by photocuring is significantly improved, and the shrinkage rate is greatly reduced, breaking through the technical bottlenecks such as low refractive index, high cost, high shrinkage rate, and a large amount of waste of conventional binders, thus fully meeting the usage requirements and greatly expanding its application fields.

[0063] Example 1

[0064] (1) Prepare a binary or polyhydric allyl alcohol composition with hydroxyl groups

[0065] Take 30 parts by weight of plastic oil, and then transfer the mixture to a stainless-steel Parr reactor. Purge the reactor twice with Ar at room temperature (25 °C). After the system reaches 100 °C, introduce syngas (CO / H2 = 1, molar ratio) into the reactor;

[0066] Stir the mixture at 800 rpm throughout the process, and the reaction time is 25 min;

[0067] After that, load the catalyst (20 wt% Ni / SiO2) into a stainless-steel tube reactor, and then pretreat it at 350 °C (heating rate: 5 °C / min) for 3 h with a hydrogen flow rate of 50 cm 3 / min (SCCM);

[0068] Then cool the reactor to 100 °C and pressurize it to 70 bar (H2) through a back-pressure regulator;

[0069] Introduce 40 parts by weight of the hydroformylation product through an HPLC pump and react for 6 h to obtain an allyl alcohol composition.

[0070] (2) Preparation of a binary acrylic acid composition with a carboxyl group

[0071] Weigh 26 parts by weight of palladium acetate and 50 parts by weight of 1,4-bis(diphenylphosphino)butane, and place them in a clean and dry glass liner equipped with a drying stir bar;

[0072] Install the glass liner inside a stainless-steel Parr autoclave and close the autoclave. Connect the autoclave to a Schlenk line and perform five cycles of evacuation and nitrogen filling;

[0073] Using standard Schlenk techniques, add a cryopump thawed solution of 12 parts by weight of formic acid in dry 1,2-dichloroethane (DCE), and stir the mixture for 30 min;

[0074] Then use the standard Schlenk procedure to add the required volume of degassed and dried plastic oil, 25 parts by weight, close the autoclave and disconnect it from the Schlenk line. Transfer the autoclave to a polymerization block and connect it to a gas line. Flush the lines connected to the autoclave with nitrogen (N2) (3 × 30 bar);

[0075] Flush the autoclave with carbon monoxide (CO), then fill it with CO to 45 bar, stir the autoclave at 300 rpm and heat it at the required temperature (80 °C) for 14 h to obtain a binary acrylic acid composition.

[0076] (3) Preparation of (bromo)phenyl acrylate oligomer

[0077] Copolymerizing a (bromo)phenyl acrylate monomer having 6 alkyl carbon chains at the end of the ester group, a (bromo)phenyl acrylate monomer having an epoxy group, a (bromo)phenyl acrylate monomer having a hydroxyl group, and a (bromo)phenyl acrylate monomer having a high Tg to obtain a (bromo)phenyl acrylate oligomer;

[0078] The copolymerization reaction conditions are as follows: heating to 80° C., adding nitrogen protection, and heating for 3 hours under the action of 1.2 parts by weight of initiator benzoyl peroxide;

[0079] Wherein, based on the mass parts of each component monomer, the (bromo)phenyl acrylate monomer with 6 alkyl carbon chains at the end of the ester group is 70 parts, the (bromo)phenyl acrylate monomer with epoxy group is 30 parts, the (bromo)phenyl acrylate monomer with hydroxyl group is 40 parts, and the (bromo)phenyl acrylate monomer with high Tg is 50 parts;

[0080] The oligomer monomers involved are purchased directly from the website, and the specific source is (Alpha) Zhengzhou Alpha Chemical Co., Ltd.

[0081] (4) Preparation of high refractive index materials

[0082] 28 parts by weight of oleic acid and 45 parts by weight of titanium dioxide were added to a pre-dried round-bottom flask. In order to work in an air-free environment, the oleic acid was first degassed with three vacuum / nitrogen cycles and then further degassed at 120°C for 2h. The mixture was then cooled to 90°C under a nitrogen stream.

[0083] When the target temperature is reached, 4 parts by weight of tetramethyltetraphenylcyclotetrasiloxane is added at one time. After 5 minutes, 1 part by weight of an aqueous solution of trimethylamine oxide is injected at one time. The flask is heated to 100° C. at a heating rate of about 26° C. / min, and then reacted for 22 hours under vigorous stirring.

[0084] The solution changed from a clear light yellow mixture to a milky solution, and then the crude product was centrifuged to precipitate a white solid consisting of oleic acid-capped TiO2 NCs;

[0085] The particles were precipitated several times in ethanol to remove excess ligand and finally dispersed in DCM;

[0086] 32 parts by weight of mPEO (molecular weight = 5000 g / mol) were dissolved in dry DCM and added dropwise to a solution of 1 part by weight of phosphoryl chloride and 1.6 parts by weight of triethylamine in an ice bath. The mixture was warmed to 20° C. and stirred for 1.5 h. Under argon at 40° C., 42 parts by weight of sodium sulfide solution were added to a vigorously stirred mixture of 4 parts by weight of dichloroethane and 60 parts by weight of degassed deionized water. The reaction mixture was further stirred at 40° C. for 14 h to obtain a high refractive index material.

[0087] (5) Preparation of the adhesive: Mix an allyl alcohol composition, a binary acrylic acid composition, a (bromo)phenyl acrylate oligomer, and a high refractive index material in a mass ratio of 10:10:70:10, and irradiate for 3 minutes under a high-pressure mercury lamp with a light intensity of 600 mW / cm 2 to obtain an adhesive composition.

[0088] (6) Based on 100 parts by weight of the adhesive composition, the photoinitiator TPO, the crosslinking agent hydroxypropyl acrylate, and the antistatic agent ethoxylated laurylamide are mechanically mixed in proportions of 1 part by weight, 0.5 part by weight, and 0.01 part by weight respectively;

[0089] After mixing the above components evenly, the curable optical adhesive is obtained by ultraviolet irradiation under a nitrogen atmosphere.

[0090] See the technical roadmap Figure 1 ; See the nuclear magnetic spectrum of the prepared binary allyl alcohol Figure 2 , and see the nuclear magnetic spectrum of the prepared binary acrylic acid Figure 3 .

[0091] Example 2

[0092] According to the method of Example 1, the difference is:

[0093] In step (6): The photoinitiator TPO, the crosslinking agent hydroxypropyl acrylate, and the antistatic agent ethoxylated laurylamide are mechanically mixed in proportions of 2 parts by weight, 1.5 parts by weight, and 1 part by weight respectively. The test results are shown in Table 1.

[0094] Example 3

[0095] (1) Preparation of a binary or polyallyl alcohol composition with hydroxyl groups

[0096] Take 50 parts by weight of plastic oil, then transfer the mixture to a stainless steel Parr reactor, purge the reactor 3 times with Ar at room temperature (25 °C), and after the system reaches 110 °C, introduce synthesis gas (CO / H2 = 1.2, molar ratio) into the reactor;

[0097] Stir the mixture at 900 rpm throughout the process, and the reaction time is 35 min;

[0098] After that, load the catalyst (20 wt% Ni / SiO2) into a stainless steel tube reactor, and then pretreat it at 400 °C (heating rate: 8 °C / min) for 4 h, with a hydrogen flow rate of 60 cm 3 / min (SCCM);

[0099] Then cool the reactor to 100 °C and pressurize it to 85 bar (H2) through a back-pressure regulator;

[0100] Introduce 50 parts by weight of the hydroformylation product through an HPLC pump and react for 7 h to obtain an allyl alcohol composition.

[0101] (2) Prepare a dicarboxylic acrylic acid composition with a carboxyl group

[0102] Weigh 40 parts by weight of palladium acetate and 70 parts by weight of 1,4-bis(diphenylphosphino)butane and place them in a clean and dry glass liner equipped with a dried stirring bar;

[0103] Install the glass liner in a stainless-steel Parr autoclave and close the autoclave. Connect the autoclave to a Schlenk line and perform five vacuum and nitrogen filling cycles;

[0104] Using standard Schlenk techniques, add a frozen pump-thawed solution of 16 parts by weight of formic acid in dry 1,2-dichloroethane (DCE) and stir the mixture for 30 min;

[0105] Then use the standard Schlenk procedure to add the required volume of degassed and dried plastic oil, 35 parts by weight, close the autoclave and disconnect it from the Schlenk line. Transfer the autoclave to a polymerization block and connect it to a gas line. Flush the line connected to the autoclave with nitrogen (N2) (3 × 30 bar);

[0106] Flush the autoclave with carbon monoxide (CO), then charge it with CO to 55 bar, stir the autoclave at 350 rpm and heat it at the required temperature for 16 h to obtain a dicarboxylic acrylic acid composition.

[0107] (3) Prepare a (bromo)phenyl acrylate oligomer

[0108] Copolymerize a (bromo)phenyl acrylate monomer with an alkyl chain of 12 carbon atoms at the ester group end, a (bromo)phenyl acrylate monomer with an epoxy group, a (bromo)phenyl acrylate monomer with a hydroxyl group, and a (bromo)phenyl acrylate monomer with a high Tg to obtain a (bromo)phenyl acrylate oligomer;

[0109] Among them, the copolymerization reaction conditions are: under the action of 2 parts by weight of initiator benzoyl peroxide, heat to 80 °C, add nitrogen protection, and heat for 3 hours;

[0110] Among them, based on the mass parts of each component monomer, 30 parts of (bromo)phenyl acrylate monomer with an ester group terminal carbon chain of 12 alkyl groups, 1 part of (bromo)phenyl acrylate monomer with an epoxy group, 40 parts of (bromo)phenyl acrylate monomer with a hydroxyl group, and 10 parts of (bromo)phenyl acrylate monomer with a high Tg; the oligomer monomers involved are directly purchased from the website, and the specific source is (Alpha) Zhengzhou Alpha Chemical Co., Ltd.

[0111] (4) Preparation of high refractive index material

[0112] Add 35 parts by weight of oleic acid to a pre-dried round-bottom flask. In order to work in an air-free environment, the oleic acid is first degassed with three vacuum / nitrogen cycles and then further degassed at 120 °C for 2 h; then the mixture is cooled to 90 °C under a nitrogen stream;

[0113] When the target temperature is reached, add 7 parts by weight of tetramethyltetraphenylcyclotetrasiloxane all at once. After 5 min, inject 1.5 parts by weight of an aqueous solution of trimethylamine oxide all at once, and heat the flask to 110 °C at a heating rate of about 34 °C / min, and then react under vigorous stirring for 28 h;

[0114] The solution changes from a clear pale yellow mixture to a milky white solution, and then the crude product is centrifuged to precipitate a white solid composed of titanium dioxide NC covered with oleic acid;

[0115] The particles are precipitated several times in ethanol to remove excess ligands and are finally dispersed in hexane, chloroform or DCM;

[0116] Dissolve 40 parts by weight of mPEO in dry DCM and add dropwise to a solution of 1.5 parts by weight of phosphoryl chloride and 2 parts by weight of triethylamine in an ice bath;

[0117] Warm the mixture to 28 °C and stir for 2 h. Under argon at 60 °C, add 50 parts by weight of a sodium sulfide solution to a vigorously stirred mixture of 6 parts by weight of dichloroethane and 80 parts by weight of degassed deionized water. Stir the reaction mixture at 60 °C for a further 22 h to obtain a high refractive index material.

[0118] (5) Preparation of the adhesive: Mix the allyl alcohol composition, the binary acrylic acid composition, the (bromo)phenyl acrylate oligomer and the high refractive index material in a mass ratio of 10:10:70:10, and irradiate with a high-pressure mercury lamp with a wavelength of 320 - 400 nm and a light intensity of 600 mW / cm 2 for 3 minutes to obtain the adhesive composition.

[0119] (6) Based on 100 parts by weight of the binder composition, the photoinitiator TPO, the crosslinking agent hydroxypropyl acrylate, and the antistatic agent ethoxylated laurylamide are mechanically mixed in a ratio of 1 part by weight, 0.5 part by weight, and 0.01 part by weight, respectively;

[0120] After mixing the above components evenly, they are irradiated with ultraviolet light with other components in a nitrogen atmosphere to obtain the post-curable optical adhesive.

[0121] Example 4

[0122] According to the method of Example 3, the difference is:

[0123] In step (6): The photoinitiator, crosslinking agent, and antistatic agent are mechanically mixed in a ratio of 2 parts by weight, 1.5 parts by weight, and 1 part by weight, respectively. The test results are shown in Table 1.

[0124] Example 5

[0125] (1) Prepare a binary or polyhydric allyl alcohol composition with hydroxyl groups

[0126] Take 40 parts by weight of plastic oil, then transfer the mixture to a stainless steel Parr reactor, purge the reactor 3 times with Ar at room temperature (25 °C), and after the system reaches 105 °C, introduce syngas (CO / H2 = 1.1, molar ratio) into the reactor;

[0127] The mixture is stirred at 850 rpm throughout the process, and the reaction time is 30 min;

[0128] After that, the catalyst (20 wt% Ni / SiO2) is loaded into a stainless steel tube reactor, and then pretreated at 375 °C (heating rate: 6 °C / min) for 3.5 h, and the hydrogen flow rate is 55 cm 3 / min (SCCM);

[0129] Then cool the reactor to 100 °C and pressurize it to 80 bar (H2) through a back pressure regulator;

[0130] Introduce 45 parts by weight of the hydroformylation product through an HPLC pump and react for 6.5 h to obtain the allyl alcohol composition.

[0131] (2) Prepare a binary acrylic acid composition with carboxyl groups

[0132] Weigh 35 parts by weight of palladium acetate and 60 parts by weight of 1,4-bis(diphenylphosphino)butane, and put them into a clean and dry glass liner equipped with a dried stirring rod;

[0133] Install the glass lining inside the stainless steel Parr autoclave and close the autoclave. Connect the autoclave to the Schlenk line and perform five evacuation and nitrogen filling cycles;

[0134] Add a cryopump thawed solution of 14 parts by weight of formic acid in dry 1,2 - dichloroethane (DCE) using standard Schlenk techniques and stir the mixture for 30 min;

[0135] Then add the required volume of 30 parts by weight of degassed and dried plastic oil using standard Schlenk procedures, close the autoclave and disconnect it from the Schlenk line, transfer the autoclave to the polymerization block and connect it to the gas line, and flush the lines connected to the autoclave with nitrogen (N2) (3×30 bar);

[0136] Flush the autoclave with carbon monoxide (CO), then charge CO to 50 bar, stir the autoclave at 325 rpm and heat at the required temperature for 15 h to obtain a binary acrylic acid composition.

[0137] (3) Preparation of (bromo)phenyl acrylate oligomer

[0138] Copolymerize the (bromo)phenyl acrylate monomer with an alkyl chain of 4 carbon atoms at the ester group end, the (bromo)phenyl acrylate monomer with an epoxy group, the (bromo)phenyl acrylate monomer with a hydroxyl group, and the (bromo)phenyl acrylate monomer with a high Tg to obtain a (bromo)phenyl acrylate oligomer;

[0139] Among them, the copolymerization reaction conditions are: under the action of 1.6 parts by weight of initiator benzoyl peroxide, heat to 80 °C, add nitrogen protection, and heat for 3 hours;

[0140] Among them, the mass parts of each component monomer are: 50 parts of (bromo)phenyl acrylate monomer with an alkyl chain of 4 carbon atoms at the ester group end; 15 parts of (bromo)phenyl acrylate monomer with an epoxy group; 20 parts of (bromo)phenyl acrylate monomer with a hydroxyl group; 35 parts of (bromo)phenyl acrylate monomer with a high Tg; the oligomer monomers involved are directly purchased from the website, and the specific source is (Alpha) Zhengzhou Alpha Chemical Co., Ltd.

[0141] (4) Preparation of high refractive index material

[0142] Add 32 parts by weight of oleic acid to a pre - dried round - bottom flask. To work in an air - free environment, oleic acid is first degassed with three vacuum / nitrogen cycles and then further degassed at 120 °C for 2 h; then cool the mixture to 90 °C under a nitrogen stream;

[0143] When the target temperature is reached, 6 parts by weight of tetramethyltetraphenylcyclotetrasiloxane are added at one time. After 5 min, 1.2 parts by weight of an aqueous solution of trimethylamine oxide are injected at one time. The flask is heated to 105 °C at a heating rate of about 30 °C / min, and then reacted for 24 h under vigorous stirring;

[0144] The solution changes from a clear pale yellow mixture to a milky white solution, and then the crude product is centrifuged to precipitate a white solid composed of titanium dioxide NCs covered with oleic acid;

[0145] The particles are precipitated several times in ethanol to remove the excess ligands and are finally dispersed in hexane, chloroform or DCM;

[0146] 36 parts by weight of mPEO are dissolved in dry DCM and added dropwise to a solution of 1.3 parts by weight of phosphoryl chloride and 1.8 parts by weight of triethylamine in an ice bath. The mixture is warmed to 24 °C and stirred for 1.75 h. Under argon at 50 °C, 46 parts by weight of a sodium sulfide solution are added to a vigorously stirred mixture of 5 parts by weight of dichloroethane and 70 parts by weight of degassed deionized water. The reaction mixture is further stirred at 50 °C for 16 h to obtain a high refractive index material.

[0147] (5) Preparation of the adhesive:

[0148] An allyl alcohol composition, a binary acrylic acid composition, a (bromo)phenyl acrylate oligomer and a high refractive index material are mixed in a mass ratio of 10:10:70:10, and irradiated with a high-pressure mercury lamp at a wavelength of 320 - 400 nm and a light intensity of 600 mW / cm 2 for 3 minutes to obtain an adhesive composition.

[0149] (6) Based on 100 parts by weight of the adhesive composition, the photoinitiator TPO, the crosslinking agent hydroxypropyl acrylate and the antistatic agent ethoxylated laurylamide are mechanically mixed in ratios of 1 part by weight, 0.5 part by weight and 0.01 part by weight respectively; after mixing the above components evenly, the curable optical adhesive is obtained by ultraviolet irradiation with other components in a nitrogen atmosphere.

[0150] Example 6

[0151] According to the method of Example 5, the difference is:

[0152] In step (6): The photoinitiator TPO, the crosslinking agent hydroxypropyl acrylate and the antistatic agent ethoxylated laurylamide are mechanically mixed in ratios of 2 parts by weight, 1.5 parts by weight and 1 part by weight respectively. The test results are shown in Table 1.

[0153] Example 7

[0154] (1) Preparation of a binary or polyhydric allyl alcohol composition with hydroxyl groups

[0155] Take 10 parts by weight of plastic oil, then transfer the mixture to a stainless-steel Parr reactor, purge the reactor 3 times with Ar at room temperature (25 °C), and after the system reaches 80 °C, introduce syngas (CO / H2 = 1.1, molar ratio) into the reactor;

[0156] The mixture is stirred at 700 rpm throughout the process, and the reaction time is 20 min;

[0157] After that, load the catalyst (20 wt% Ni / SiO2) into a stainless-steel tube reactor, and then pretreat it at 100 °C (heating rate: 2 °C / min) for 3.5 h, with a hydrogen flow rate of 50 cm 3 / min (SCCM);

[0158] Then cool the reactor to 100 °C and pressurize it to 60 bar (H2) through a back-pressure regulator;

[0159] Introduce 20 parts by weight of the hydroformylation product through an HPLC pump and react for 9 h to obtain an allyl alcohol composition.

[0160] (2) Preparation of a binary acrylic acid composition with a carboxyl group

[0161] Weigh 20 parts by weight of palladium acetate and 40 parts by weight of 1,4-bis(diphenylphosphino)butane, and place them in a clean and dry glass liner equipped with a drying stir bar;

[0162] Install the glass liner inside a stainless-steel Parr autoclave and close the autoclave. Connect the autoclave to a Schlenk line and perform five vacuum and nitrogen filling cycles;

[0163] Use standard Schlenk techniques to add a cryopump thawed solution of 10 parts by weight of formic acid in dry 1,2-dichloroethane (DCE), and stir the mixture for 30 min;

[0164] Then use the standard Schlenk procedure to add the required volume of 20 parts by weight of degassed and dried plastic oil, close the autoclave and disconnect it from the Schlenk line, transfer the autoclave to a polymerization block and connect it to a gas line, and rinse the line connected to the autoclave with nitrogen (N2) (3 × 30 bar);

[0165] Flush the autoclave with carbon monoxide (CO), then fill it with CO to 40 bar, stir the autoclave at 200 rpm and heat it at the required temperature for 12 h to obtain a binary acrylic acid composition.

[0166] (3) Preparation of (bromo)phenyl acrylate oligomer

[0167] It is obtained by copolymerizing a (bromo)phenyl acrylate monomer with 6 alkyl groups at the ester group terminal carbon chain, a (bromo)phenyl acrylate monomer with an epoxy group, a (bromo)phenyl acrylate monomer with a hydroxyl group, and a (bromo)phenyl acrylate monomer with a high Tg;

[0168] Among them, the copolymerization reaction conditions are: under the action of 0.1 part by weight of initiator benzoyl peroxide, heating to 80 °C, adding nitrogen protection, and heating for 3 hours;

[0169] Among them, the mass parts of each component monomer are: 40 parts of (bromo)phenyl acrylate monomer with 6 alkyl groups at the ester group terminal carbon chain; 20 parts of (bromo)phenyl acrylate monomer with an epoxy group; 20 parts of (bromo)phenyl acrylate monomer with a hydroxyl group; 40 parts of (bromo)phenyl acrylate monomer with a high Tg;

[0170] The oligomer monomers involved are directly purchased from the website, and the specific source is (Alpha) Zhengzhou Alpha Chemical Co., Ltd.

[0171] (4) Preparation of high refractive index material

[0172] Add 20 parts by weight of oleic acid to a pre-dried round-bottom flask. In order to work in an air-free environment, the oleic acid is first degassed with three vacuum / nitrogen cycles, and then further degassed at 80 °C for 2 h; then the mixture is cooled to 90 °C under a nitrogen stream;

[0173] When the target temperature is reached, 1 part by weight of tetramethyltetraphenylcyclotetrasiloxane is added all at once. After 5 min, 0.1 part by weight of an aqueous solution of trimethylamine oxide is injected all at once. The flask is heated to 80 °C at a heating rate of about 26 °C / min, and then reacted for 18 h under vigorous stirring;

[0174] The solution changes from a clear pale yellow mixture to a milky white solution, and then the crude product is centrifuged to precipitate a white solid composed of titanium dioxide NC covered with oleic acid;

[0175] The particles are precipitated several times in ethanol to remove excess ligands and are finally dispersed in hexane, chloroform or DCM;

[0176] Dissolve 26 parts by weight of mPEO in dry DCM and add it dropwise to a solution of 0.8 part by weight of phosphoryl chloride and 1.6 parts by weight of triethylamine in an ice bath. Warm the mixture to 15 °C and stir for 1 h. Under argon at 50 °C, add 40 parts by weight of sodium sulfide solution to a vigorously stirred mixture of 2 parts by weight of dichloroethane and 70 parts by weight of degassed deionized water. Stir the reaction mixture at 40 °C for a further 14 h to obtain a high refractive index material.

[0177] (5) Preparation of the adhesive: Mix an allyl alcohol composition, a binary acrylic acid composition, a (bromo)phenyl acrylate oligomer, and a high refractive index material in a mass ratio of 10:10:70:10. Use a high-pressure mercury lamp with a wavelength of 320 - 400 nm and a light intensity of 600 mW / cm 2 Irradiate for 3 minutes to obtain the adhesive composition.

[0178] (6) Based on 100 parts by weight of the adhesive composition, the photoinitiator, crosslinking agent, and antistatic agent are mechanically mixed in ratios of 1 part by weight, 0.5 part by weight, and 0.01 part by weight respectively. After mixing the above components evenly, irradiate with ultraviolet light in a nitrogen atmosphere with other additives to obtain the post-curable optical adhesive.

[0179] Example 8

[0180] According to the method of Example 7, the difference is:

[0181] In step (5): The photoinitiator TPO, crosslinking agent hydroxypropyl acrylate, and antistatic agent ethoxylated laurylamide are mechanically mixed in ratios of 2 parts by weight, 1.5 parts by weight, and 1 part by weight respectively. The test results are shown in Table 1.

[0182] Example 9

[0183] (1) Preparation of a binary or polyallyl alcohol composition with hydroxyl groups

[0184] Take 60 parts by weight of plastic oil, then transfer the mixture to a stainless-steel Parr reactor, purge the reactor 3 times with Ar at room temperature (25 °C), after the system reaches 120 °C, introduce syngas (CO / H2 = 1.5, molar ratio) into the reactor;

[0185] Stir the mixture at 1000 rpm throughout the process, and the reaction time is 40 min;

[0186] After that, load the catalyst (20 wt% Ni / SiO2) into a stainless-steel tube reactor, then pretreat it at 400 °C (heating rate: 10 °C / min) for 12 h, and the hydrogen flow rate is 50 cm 3 / min (SCCM);

[0187] Then cool the reactor to 100 °C and pressurize it to 85 bar (H2) through a back-pressure regulator;

[0188] Introduce 70 parts by weight of the hydroformylation product through an HPLC pump and react for 12 h to obtain the allyl alcohol composition.

[0189] (2) Preparation of a binary acrylic acid composition with carboxyl groups

[0190] Weigh 40 parts by weight of palladium acetate and 80 parts by weight of 1,4-bis(diphenylphosphino)butane, and place them in a clean and dry glass liner equipped with a dried stirring bar;

[0191] Install the glass liner inside a stainless steel Parr autoclave and close the autoclave. Connect the autoclave to a Schlenk line and perform five cycles of evacuation and nitrogen filling;

[0192] Using standard Schlenk techniques, add a cryopump thawed solution of 20 parts by weight of formic acid in dry 1,2-dichloroethane (DCE), and stir the mixture for 30 min;

[0193] Then, using standard Schlenk procedures, add the required volume of degassed and dried plastic oil, 40 parts by weight, close the autoclave and disconnect it from the Schlenk line. Transfer the autoclave to a polymerization block and connect it to a gas line. Flush the lines connected to the autoclave with nitrogen (N2) (3×30 bar);

[0194] Flush the autoclave with carbon monoxide (CO), then charge it with CO to 40 bar. Stir the autoclave at 200 rpm and heat it at the required temperature for 12 h to obtain a binary acrylic acid composition.

[0195] (3) Preparation of (bromo)phenyl acrylate oligomer

[0196] It is obtained by copolymerizing (bromo)phenyl acrylate monomers with 12 alkyl carbon atoms at the ester group terminal, (bromo)phenyl acrylate monomers with epoxy groups, (bromo)phenyl acrylate monomers with hydroxyl groups, and (bromo)phenyl acrylate monomers with high Tg;

[0197] Among them, the copolymerization reaction conditions are: under the action of 1 part by weight of initiator benzoyl peroxide, heat to 80 °C, add nitrogen protection, and heat for 3 hours;

[0198] Among them, the mass parts of each component monomer are 70 parts of (bromo)phenyl acrylate monomer with 12 alkyl carbon atoms at the ester group terminal; 30 parts of (bromo)phenyl acrylate monomer with epoxy groups; 40 parts of (bromo)phenyl acrylate monomer with hydroxyl groups; 50 parts of (bromo)phenyl acrylate monomer with high Tg; The oligomer monomers involved are directly purchased from the website, and the specific source is (Alpha) Zhengzhou Alpha Chemical Co., Ltd.

[0199] (4) Preparation of high refractive index material

[0200] Add 40 parts by weight of oleic acid to a pre-dried round-bottom flask. In order to work in an air-free environment, oleic acid is first degassed with three vacuum / nitrogen cycles, and then further degassed at 120 °C for 2 h;

[0201] Then cool the mixture to 90 °C under a nitrogen stream;

[0202] When the target temperature is reached, add 1 part by weight of tetramethyltetraphenylcyclotetrasiloxane all at once; after 5 min, inject 2 parts by weight of an aqueous solution of trimethylamine oxide all at once, and heat the flask to 80 °C at a heating rate of about 40 °C / min, then react for 30 h under vigorous stirring;

[0203] The solution changes from a clear pale yellow mixture to a milky white solution, and then the crude product is centrifuged to precipitate a white solid composed of titanium dioxide NCs covered with oleic acid;

[0204] The particles are precipitated several times in ethanol to remove excess ligands and are finally dispersed in hexane, chloroform or DCM. Dissolve 48 parts by weight of mPEO in dry DCM and add dropwise to a solution of 1.6 parts by weight of phosphoryl chloride and 2 parts by weight of triethylamine in an ice bath;

[0205] Warm the mixture to 30 °C and stir for 2 h. Under argon at 80 °C, add 50 parts by weight of a sodium sulfide solution to a vigorously stirred mixture of 8 parts by weight of dichloroethane and 70 parts by weight of degassed deionized water. Stir the reaction mixture at 60 °C for a further 22 h to obtain a high refractive index material.

[0206] (5) Prepare an adhesive: Mix an allyl alcohol composition, a binary acrylic acid composition, a (bromo)phenyl acrylate oligomer and a high refractive index material in a mass ratio of 10:10:70:10, and use a high-pressure mercury lamp with a wavelength of 320 - 400 nm and a light intensity of 600 mW / cm 2 Irradiate for 3 minutes to obtain an adhesive composition.

[0207] (6) Based on 100 parts by weight of the adhesive composition, the photoinitiator TPO, the crosslinking agent hydroxypropyl acrylate and the antistatic agent ethoxylated laurylamide are mechanically mixed in ratios of 1 part by weight, 0.5 part by weight and 0.01 part by weight respectively. After mixing the above components evenly, irradiate with ultraviolet light in a nitrogen atmosphere with other components to obtain the post-curable optical adhesive.

[0208] Example 10

[0209] According to the method of Example 9, the difference is:

[0210] In step (6): The photoinitiator TPO, the crosslinking agent hydroxypropyl acrylate and the antistatic agent ethoxylated laurylamide are mechanically mixed in ratios of 2 parts by weight, 1.5 parts by weight and 1 part by weight respectively. The test results are shown in Table 1.

[0211] Example 11

[0212] According to the method of Example 1, the difference is that no cross-linking agent is added.

[0213] Example 12

[0214] According to the method of Example 7, the difference is that no photoinitiator is added.

[0215] Comparative Example 1

[0216] According to the method of Example 3, the difference is that "35 parts by weight of oleic acid" is replaced with "15 parts by weight".

[0217] Comparative Example 2

[0218] According to the method of Example 7, the difference is that

[0219] No binary or polyhydric allyl alcohol composition is added, and the corresponding binary or polyhydric acrylic acid composition: (bromo)phenyl acrylate oligomer: high refractive index material mass ratio is 20:70:10;

[0220] Other conditions are the same as those in Example 7.

[0221] Comparative Example 3

[0222] According to the method of Example 7, the difference is that

[0223] No binary or polyhydric acrylic acid composition is added, and the corresponding binary or polyhydric allyl alcohol composition: (bromo)phenyl acrylate oligomer: high refractive index material ratio is 20:70:10;

[0224] Other conditions are the same as those in Example 7.

[0225] Comparative Example 4

[0226] According to the method of Example 7, the difference is that no binary or polyhydric allyl alcohol composition and binary or polyhydric acrylic acid composition are added. Correspondingly, (bromo)phenyl acrylate oligomer and high refractive index material are mixed in a mass ratio of 90:10.

[0227] Table 1

[0228]

[0229]

[0230] It can be seen from the results in Table 1 that the present invention improves the viscosity and refractive index of the adhesive by cooperating the oligomer with specific component content, the modified titanium dioxide and the polysulfide polymer, that is, improves the strength and brightness of the adhesive; it can be seen from Examples 2, 4, 6 and Comparative Example 1 that the higher the refractive index, the better the titanium dioxide modified composite material can improve the refractive index of the adhesive, thereby improving the brightness of the adhesive; it can be seen from Examples 1, 3, 5, 11 that when the photoinitiator and the crosslinking agent are not added, the viscosity of the adhesive is low and it is difficult to obtain an adhesive with high strength. It can be seen from Comparative Examples 2-4 that the oligomer prepared from the pyrolysis product of plastic waste can increase the elasticity of the adhesive.

[0231] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that the technical solutions of the present invention can be modified or equivalently replaced without departing from the spirit and scope of the technical solutions of the present invention, and they should all be covered within the scope of the present invention.

Claims

1. A preparation method of an adhesive composition for an optical film based on waste plastics, characterized in that: Comprising, Performing an oxidation reaction on plastic oil and syngas in an inert gas. After cooling, adding a hydroformylation product and hydrogen, and performing a catalytic hydrogenation reaction under the condition of a catalyst to obtain a binary or polyhydric allyl alcohol composition with hydroxyl groups; Mixing palladium acetate with an organic solution, and adding plastic oil, formic acid and CO through a standard Schlenk technique to react to obtain a binary acrylic acid composition; Using (bromo)acrylate as a monomer to polymerize to obtain a (bromo)phenyl acrylate oligomer; Modifying TiO2 with oleic acid and mPEO, and performing ring-opening copolymerization with 1,2-dithiolane to obtain a high refractive index material; Mixing the binary or polyhydric allyl alcohol composition with hydroxyl groups, the binary acrylic acid composition, the (bromo)phenyl acrylate oligomer and the high refractive index material to obtain an adhesive composition; Mixing the adhesive composition, a photoinitiator, a crosslinking agent and an antistatic agent to obtain a post-curable optical adhesive.

2. The preparation method according to claim 1, characterized in that: The conditions of the oxidation reaction include: the reaction temperature is 80 - 120 °C, the reaction time is 20 - 40 min, and the stirring speed is 700 - 1000 rpm; The conditions for the catalytic hydrogenation reaction include: the reaction temperature is 100 to 400 °C, the reaction time is 8 to 12 h, the heating rate is 2 to 10 °C / min, the hydrogen flow rate is 50 to 60 cm 3 / min, and the pressure is 60 to 90 bar. The syngas is CO / H2 = 0.9 - 1.5, molar ratio; the inert gas is argon.

3. The preparation method according to claim 1 or 2, characterized in that: Calculated by the mass parts of raw materials, the plastic oil is 10 - 60 parts by weight, and the hydroformylation product is 20 - 70 parts by weight; The catalyst is a commercial catalyst Pt, Ni, Pd, including Ni / SiO2.

4. The preparation method according to claim 1, characterized in that: The preparation method of the binary acrylic acid composition, wherein the organic solvent is a low-carbon organic compound, including 1,4-bis(diphenylphosphinyl)butane, 1,4-bis(diphenylphosphino)butane; Based on the parts by mass of the raw materials, the plastic oil is 20 to 40 parts by weight, the organic solvent is 40 to 80 parts by weight, the palladium acetate is 20 to 40 parts by weight, the formic acid solution is 10 to 20 parts by weight, and the CO flow rate is 40 to 70 cm 3 / min.

5. The preparation method according to claim 1 or 4, characterized in that: The reaction conditions of the standard Schlenk technique include, The reaction pressure is 40 - 60 bar, the stirring rate is 200 - 400 rmp, and the reaction time is 12 - 18 h.

6. The preparation method according to claim 1, characterized in that: The (bromo)acrylate includes (bromo)phenyl acrylic acid alkyl ester, (bromo)phenyl acrylic acid alkenyl ester and (bromo)phenyl acrylic acid heterocyclic ester.

7. The preparation method according to claim 1 or 6, characterized in that: The preparation method of the high refractive index material includes, First, modifying the surface of TiO2 with oleic acid, adding tetramethyltetraphenylcyclotetrasiloxane, and modifying the surface of the modified TiO2 with trimethylamine oxide. Subsequently, mPEO (molecular weight = 5000 g / mol) is modified according to the procedure proposed by Zalipsky and reacts with oleic acid-coated TiO2; Performing copolymerization of a polysulfide polymer sodium tetrasulfide solution with the modified TiO2 in a dichloroethane solution to obtain a high refractive index material; wherein, The conditions of the modification reaction include: the reaction temperature is 80 - 120 °C, the heating rate is 20 - 40 °C / min, and the reaction time is 18 - 30 h; The oleic acid is 20 - 40 parts by weight, the tetramethyltetraphenylcyclotetrasiloxane is 1 - 10 parts by weight, and the trimethylamine oxide is 0.1 - 2 parts by weight; the mPEO is 26 - 48 parts by weight, the phosphoryl chloride is 0.8 - 1.6 parts by weight, and the triethylamine is 1.6 - 3 parts by weight; the polysulfide polymer is 30 - 50 parts by weight, the sodium tetrasulfide solution is 40 - 50 parts by weight, and the dichloroethane is 2 - 8 parts by weight.

8. The preparation method according to claim 7, characterized in that: The Zalipsky conditions include a reaction temperature of 15 to 30 °C and a reaction time of 1 to 2 h; The copolymerization reaction conditions include: a reaction temperature of 30 to 80 °C and a reaction time of 10 to 26 h.

9. The preparation method according to claim 1, characterized in that: The method for preparing the adhesive composition includes Mix an allyl alcohol composition, a binary acrylic acid composition, a (bromo)phenyl acrylate oligomer, and a high refractive index material in a mass ratio of 10:10:70:10, and irradiate with a high-pressure mercury lamp with a wavelength of 320-400 nm and a light intensity of 10-600 mW / cm 2 for 0.5-3 minutes to obtain an adhesive composition; Based on 100 parts by weight of the adhesive composition, the content of the photoinitiator is 0.5 to 3 parts by weight, the content of the crosslinking agent is 0.02 to 2 parts by weight, and the content of the antistatic agent is 0.008 to 1 part by weight; The photoinitiator includes an anionic photoinitiator or a cationic photoinitiator; The crosslinking agent enters the macromolecular structure chain during polymerization as a monomer or is added to the adhesive as a component, and includes acrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, methacrylic acid, hydroxyethyl methacrylate, hydroxypropyl methacrylate, divinylbenzene, N-methylolacrylamide, diacetone acrylamide. The antistatic agent is ethoxylated aliphatic alkylamines, including ethoxylated laurylamide, and glycerol monostearate.

10. The adhesive composition for an optical film prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Adhesive composition for optical element, optical element comprising same, and optical display device comprising same

    CN106471085B

  • Adhesive composition for optical films, adhesive layer for optical films, and optical film with adhesive layer

    CN113227297A

  • Treatment method of waste plastics and waste plastic pyrolytic oil

    CN117120580A